Wilhelmine Schaeffer-Creel Pianist and University String Orchestra, January 14, 1941 - (:unkn) unknown (My University, 1941)
Concert program for Wilhelmine Schaeffer-Creel Pianist and University String Orchestra, January 14, 1941